A support-design framework for Cooperative Robots systems in labor-intensive manufacturing processes. (October 2021) - Ronzoni, Michele; Accorsi, Riccardo; Botti, Lucia; Manzini, Riccardo
Highlights: A support-design framework for cooperative robot system in labor-intensive manufacturing. An iterative closed-loop methodology to aid the designer from a multidisciplinary perspective. Drive the designer through different digital twins for layout and control system design. Aids technical, economic, ergonomics and safety feasibility analysis. A validating case study applied to the end-of-line of a food catering production facility. Abstract: Manufacturing processes and industrial systems gradually change their traditional layouts and configurations, preparing to introduce novel integrated human-robot technologies as collaborative robots and exoskeletons. Whether mass customization of lot size and the production mix discourages the adoption of capital-intensive automation, collaborative robots become affordable and effective and a hotspot of the debate on manufacturing systems. This paper provides a novel support-design framework for the cooperative robot system in labor-intensive manufacturing processes to aid layout and task scheduling design. Through an iterative closed-loop methodology, this framework explores the impact of a cooperative robot in a labour-intensive manufacturing system like the production facility of a food service company. The framework leads the designer through the re-layout of the end-of-line, the economic and technical feasibility analyses, using simulation to estimate payback and ergonomics benefits for workers. Within the proposed layout, we state that adopting a cooperative cobot for the end-of-line is affordable and ergonomically convenient without representing a safety threat for workers. The testbed confirms the framework as an enabling tool for human-robot technologies integration in current manufacturing systems under budget and workers-driven constraints.